Thermal-stability resonators for visible light full-spectrum perfect absorbers. (15th September 2020) - Zhong, Haozong; Liu, Zhengqi; Tang, Peng; Liu, Xiaoshan; Zhan, Xuefeng; Pan, Pingping; Tang, Chaojun
Graphical abstract: A broadband perfect absorber is numerically demonstrated via the refractory material resonators. The excellent absorption efficiency is with the average A > 94% in the wavelength range from 380 nm to 760 nm (the full visible region), suggesting the impressive capability of energy harvesting, micro-fluidic thermal disinfect, local high-temperature process. Highlights: Perfect light absorption is desirable for applications related to photo-electrical effects, photo-thermal process. Excellent absorption with the average A  > 94% is achieved in the visible full-spectrum region. The TiO2 /TiN with impressive thermal stability have been used as the resonators. These findings pave new insights for nano-scale/micro-fluidic photo-thermal process, thermal disinfect, etc. Abstract: Perfect light absorption is desirable for applications in the devices related to photo-electrical effects, photo-thermal process and photo-chemical/catalysis solutions, etc. In this work, we propose and demonstrate a feasible way to achieve broadband perfect absorption in the full visible range based on the refractory material resonators. This structure shows excellent absorption efficiency with the average absorption up to 94% in the wavelength range from 380 nm to 760 nm (the visible region), suggesting the impressive capability of energy harvesting. The photonic cavity mode and the dipolar plasmon resonance by the half-cylinder cavity structure are the main contributions for the broadband absorption. The full-spectrum visible light absorption is observed to be maintained in a wide angle range under the oblique illumination. The high absorption is also retained under different polarization states. Moreover, the resonant materials such as titanium dioxide (TiO2 ) and titanium nitride (TiN) have impressive thermal stability due to their high melting points. These findings pave new insights on the refractory perfect visible light absorber for nano-scale photo-thermal process, micro-fluidic thermal disinfect and local high-temperature process, etc.